The Prevalence of Trauma Injuries From Neighboring Countries Transferred to Iran - Hadi Khoshmohabat; Hamid Reza Rasouli; Mohammad Javad Forozanmehr; Mohammad Hosein Kalantar Motamedi; Masoud Saghafinia (International Journal of Travel Medicine and Global Health, 2017)
Introduction: In recent years, the prevalence of attacks perpetrated by humans against other humans has increased worldwide. The injuries suffered by attack victims are severe and multi-organ. Iran’s neighboring countries have been the scenes of attacks in the recent past. This study assessed the type and severity of injuries sustained by victims transferred to Iran during the time period 2005-2007. Methods: This study was conducted on injured civilians transferred to hospitals in Iran. Data regarding cause of injury, type and severity of injuries, diagnostic-therapeutic interventions, and patient outcomes was collected and statistically analyzed using SPSS version 14 software. Results: In the studied time period, 214 attack victims were transferred to 3 Level 1 trauma centers in Iran. The mechanisms of injury were explosion in 130 cases, gunshot in 48, and other causes in the remaining victims. The mean Injury Severity Score (ISS) was 5.91 ± 4.54 (range = 1-34), and the median was 4; 109 cases (51%) had an ISS between 1 and 8, 73 cases (34%) were scored between 9 and 14, 15 cases (7%) were scored from 16 to 24, and 17 cases (8%) had an ISS ≥25. In terms of the number of injured organs, 42 patients (20%) had one, 124 (58%) had 2, 36 (17%) had 3, and 12 patients (5%) had 4 or more injured organs. Procedures included 86 orthopedic, 25 general surgical, 21 ear, nose, and throat (ENT), 18 plastic, 15 neurosurgical, and 10 ophthalmic operations; 25 patients received psychiatric counseling. The mean (±SD) hospital stay was 13.43 (±19.76) days (range = 1-230). Conclusion: The injury pattern in attacks is more severe and differs from other traumas. The medical team should have adequate knowledge in this respect to provide comprehensive healthcare.